Future teachers debate charter schools on Facebook: analysing their political subjectivities. Issue 1 (2nd January 2018) - Nairn, Karen; Anderson, Vivienne; Blanch, Keely
ABSTRACT: We argue that Garrett and Segall's concepts of 'doing school' and 'pushing back' are valuable tools for analysing pre-service teachers' political views of neoliberal education reforms such as the introduction of charter schools. We extend Garrett and Segall's conceptualization by hybridizing 'doing school' and 'pushing back' in order to move beyond a simplistic celebration of student resistance, which often overlooks forms of resistance that are compliant with the status quo, in this case the neoliberal status quo. We analyse participants' political views as they emerged in a debate about charter schools in New Zealand. Garrett and Segall's concepts, in conjunction with poststructuralist theories of subjectivity, are deployed as analytical tools for understanding the complexity of students' political subjectivities in a debate conducted on a Facebook page set up for that purpose.